An essential Trypanosoma brucei protein kinase: a functional analysis of regulation and the identification of inhibitors - Parsons, Marilyn; Parsons, Ben; Dean, Marissa; DeRocher, Amy E.; Islam, Zeba; Maly, Dustin J.; Jensen, Bryan C. (Frontiers in Parasitology, 2023)
The protein serine/threonine kinase AEK1 is essential in the pathogenic stage of Trypanosoma brucei, the causative agent of African trypanosomiasis. AEK1 is a member of the AGC protein kinase family, although it is not closely related to a specific human AGC kinase. Our previous chemical genetic studies showed that targeted inhibition of AEK1 in parasites expressing analog-sensitive AEK1 blocked parasite growth and enhanced survival of infected mice. We now show that less than five percent of the live cells present after a 24 hour exposure to the inhibitory analog can clonally expand, further validating AEK1 as a drug target. As a prelude to the discovery of AEK1-targeted therapeutics, we screened a panel of protein kinase inhibitors for binding to AEK1 and identified several hit compounds. To further understand how AEK1 is regulated, we used site-directed mutagenesis and functional complementation analysis to test candidate regulatory sites corresponding to motifs identified in other AGC kinases.Alanine substitutions at the four known phosphorylation sites showed that one of the two in the activation loop is essential while the other is dispensable. The two phosphosites in the C-terminal extension are required for full function. Substitutions of the phosphomimetic aspartic acid all maintained function, except for the essential phosphoserine in the activation loop. Activity of many AGC kinases is facilitated by a hydrophobic motif near the C-terminus and an allosteric site termed the PIF pocket, both of which are conserved in AEK1. As we show here, they are also essential for AEK1 function. Parasites with defective AEK1 all showed reduced proliferation and defects in cytokinesis, although tested mutations differed in the extent of cell death. Kinase activity (using a non-physiological substrate ) of immunoprecipitated mutant proteins from T. brucei paralleled the complementation studies, except for one phosphorylation site mutant that showed reduced trans-phosphorylation activity. We observed that AEK1 is cytoplasmic, residing in puncta that are distinct from glycosomes and acidocalcisomes. These data raise the possibility that localization may also play a role in functional activity.